KOMUNIKASI BUDAYA MASYARAKAT DESA TOMPOBULU DALAM MELESTARIKAN ADAT KARAMPUANG DI KECAMATAN BULUPODDO KABUPATEN SINJAI - Fahrul Ridwan , Andi; Hadawiah, Hadawiah; Ahdan, Ahdan (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The purpose of this study is to find out how the cultural communication of the Tompobulu village community in preserving the Karampuang custom in Bulupoddo sub-district, Sinjai district and how the traditional Karampuang traditional food is for the Tompobulu village community. This research lasted for 1 month and is located in Tompobulu Village, Bulupoddo District, Sinjai Regency. The informants in this study amounted to 4 people. The research method used is a qualitative research method with ethnographic studies with data collection techniques carried out in 2 ways, namely, primary data and secondary data. The method of data collection by conducting observations, interviews, and documentation. From the results of the study, it can be seen that the cultural communication of the Tompobulu Village community in preserving Karampuang traditional culture cannot be separated from the concept of leadership of the Karampuang indigenous people led by Arung or To Matoa with the help of Gella, Sanro and Guru. They are known by the term ade' eppa as the highest institution which is the last place in making decisions to resolve all problems in the customary area. The traditional food of the Karampuang indigenous people is to commemorate their ancestors, for mappakaraja (land, wind, fire and water) because the Karampuang people think that these four are the source of their life, as well as to strengthen the relationship between the Karampuang indigenous people and the village community tompobulu in general.